A Criminological Interpretation of Kip Kinkel - Oleksy, Ernest M (2019)
Kip Kinkel, responsible for the Thurston High School Shooting, made headlines for his criminality in the late '90s. Whenever a tragedy like the aforementioned one occurs, researchers and law enforcement attempt to hypothesize and theorize why a particular individual resorted to violent crime, and if such occurrences can be predicted and suppressed in the future. This article offers numerous theoretical explanations to Kinkel's behavior, analyzing his background, lifestyle, and information provided by himself and other who knew him